PEMBERDAYAAN PADA IBU TENTANG ANTICIPATORY GUIDANCE SEBAGAI UPAYA MENGOPTIMALKAN TUMBUH KEMBANG ANAK DI PONKESDES RANDUBANGU WILAYAH KERJA UPT MOJOSARI MOJOKERTO: PEMBERDAYAAN PADA IBU TENTANG ANTICIPATORY GUIDANCE SEBAGAI UPAYA MENGOPTIMALKAN TUMBUH KEMBANG ANAK DI PONKESDES RANDUBANGU WILAYAH KERJA UPT MOJOSARI MOJOKERTO - Anggreni, Dhonna; Siwi Hety, Dyah; Yuni Susanti, Ika (JCS, 2024)
The growth and development of children is determined by how they care for and care for their parents. In order to be able to face every problem and challenge that may occur in each child's development, parents need important guidance that can be used as a guide in providing appropriate care, which is called anticipatory guidance. This empowerment activity aims to provide experience and knowledge to mothers about the efforts that mothers can make and prepare to face problems that may arise at every stage of the child's development, and so that mothers are also able to provide appropriate care at every stage of the child's development. This community service activity was carried out at the Randubangu Ponkesdes which is the working area of ​​the Mojosari Mojokerto Community Health Center. Activities are carried out by providing counseling, as well as conducting questions and answers and discussions. From the results of the activity evaluation, it was found that mothers' knowledge and understanding regarding anticipatory guidance increased. The hope of this activity is that mothers are better prepared to face all the problems and stages of children's development so that children's growth and development can be more optimal.